2005
DOI: 10.1002/adem.200500013
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Corrosion and Protection of Magnesium Alloys

Abstract: Magnesium alloys are advanced light structural and functional materials being increasingly used in the automotive, aerospace, electronic, and energy industries. However, their corrosion performance at the current stage of development is still not good enough for increasingly diverse practical applications. The Cooperative Research Centre for Cast Metals Manufacturing (CAST) in Australia is one of the most active research organizations in the world established to cope with the problems associated with the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
466
2
18

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 814 publications
(496 citation statements)
references
References 72 publications
10
466
2
18
Order By: Relevance
“…In fact, magnesium alloys normally suffer from nonuniform corrosion attack. [1] Many factors can cause pitting corrosion damage of magnesium alloys, such as the non-uniformly formed corrosion product film, the micro-galvanic effect of impurity particles and secondary phases within the matrix phase as well as non-uniformity of alloy composition. Previous studies [12] showed that under dynamic conditions, the protective film was not stable, and uniform corrosion at a much higher rate was observed for high solution flow rates.…”
Section: Degradation Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, magnesium alloys normally suffer from nonuniform corrosion attack. [1] Many factors can cause pitting corrosion damage of magnesium alloys, such as the non-uniformly formed corrosion product film, the micro-galvanic effect of impurity particles and secondary phases within the matrix phase as well as non-uniformity of alloy composition. Previous studies [12] showed that under dynamic conditions, the protective film was not stable, and uniform corrosion at a much higher rate was observed for high solution flow rates.…”
Section: Degradation Behaviourmentioning
confidence: 99%
“…The poor corrosion resistance of magnesium and magnesium alloys is regarded as a major drawback, and significant effort has been focused on improving this. [1][2][3] However, the high reactivity of magnesium alloys in corrosive media can be used to advantage in biomedical applications, particularly in temporary implants where the capacity of a material for bio-degradation is one of the most sought after properties. Indeed, permanent implant materials, such as stainless steel, titanium alloys or Nitinol (55Ni-45Ti), are the only choices currently available for hard tissue implantation.…”
mentioning
confidence: 99%
“…The poor corrosion resistance depends on: (1) impurities and/or secondary phases and (2) the quality of the oxide films on the Mg surface ( Ref 3,9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Also, zinc is one of themost abundant nutritionally essential elements in the human body and released Zn ions can be easily absorbed [20,21]. Usually, the addition of zirconium can obviously refine the grains of magnesium alloys and thereby contributes to the strength and corrosion resistance of the alloys [22][23][24].…”
Section: Introductionmentioning
confidence: 99%